Comparative transcriptome analysis identified ChlH and POLGAMMA2 in regulating yellow-leaf coloration in Forsythia - Zhang, Man; Shen, Jianshuang; Wu, Yutong; Zhang, Xiaolu; Zhao, Zhengtian; Wang, Jia; Cheng, Tangren; Zhang, Qixiang; Pan, Huitang (Frontiers in Plant Science, 2022)
Leaf color is one of the most important features for plants used for landscape and ornamental purposes. However, the regulatory mechanism of yellow leaf coloration still remains elusive in many plant species. To understand the complex genetic mechanism of yellow-leaf Forsythia, we obtained a hybrid population by crossing yellow-leaf cultivar F. koreana ‘Suwon Gold’ with green-leaf F. ‘Courtaneur’. Physiological and cytological analyses demonstrated that yellow-leaf progenies were chlorophyll deficient with defected chloroplast structure. With comparative transcriptome analysis, we identified a number of candidate genes differentially expressed between yellow-leaf and green-leaf Forsythia plants. Among these genes, we further screened out two candidates, ChlH (magnesium chelatase Subunit H) and POLGAMMA2 (POLYMERASE GAMMA 2), with consistent relative-expression pattern between different colored plants. To verify the gene function, we performed virus-induced gene silencing assays and observed yellow-leaf phenotype with total chlorophyll content reduced by approximately 66% and 83% in ChlH-silenced and POLGAMMA2-silenced plants respectively. We also observed defected chloroplast structure in both ChlH-silenced and POLGAMMA2-silenced Forsythia. Transient over-expression of ChlH and POLGAMMA2 led to increased chlorophyll content and restored thylakoid architecture in yellow-leaf Forsythia. With transcriptome sequencing, we detected a number of genes related to chlorophyll biosynthesis and chloroplast development that were responsive to the silencing of ChlH and POLGAMMA2. To summarize, ChlH and POLGAMMA2 are two key genes that possibly related to yellow-leaf coloration in Forsythia through modulating chlorophyll synthesis and chloroplast ultrastructure. Our study provided insights into the molecular aspects of yellow-leaf Forsythia and expanded the knowledge of foliage color regulation in woody ornamental plants.